Altered frontal EEG asymmetry in obsessive‐compulsive disorder. (28th March 2014) - Ischebeck, Moritz; Endrass, Tanja; Simon, Daniela; Kathmann, Norbert
Abstract Hemispheric topography of alpha band power in the electroencephalogram has been linked to approach/avoidance motivation and may index the risk for anxiety disorders and depression. We quantified lower alpha band power (8–10 Hz) in 20 patients with obsessive‐compulsive disorder (OCD) and 20 matched healthy controls during blocks of rest and presentation of neutral, aversive, and OCD‐related pictures. Compared to the control group, OCD patients showed altered asymmetry, with frontal alpha power in the 8–10 Hz band being more dominant in the left hemisphere across all conditions. This alteration was not observed over parietal areas, and also did not show in the upper alpha, and the theta and beta bands. This change in hemispheric topography of lower alpha band power supports the hypothesis of relatively increased avoidance motivation in OCD. Altered asymmetry appears to be traitlike in OCD, suggesting a link to depressive disorders.